Risk Factors for Helminth Infection in Farmers : Literature Review - Enggal Hadi Kurniyawan (Politeknik Kesehatan Kementerian Kesehatan Banten, 2024)
Worm infection is a serious health problem in many countries, especially in areas with poor sanitation. The factors that contribute to worm infection can vary, including environmental factors and human behavior. This study aims to collect and analyze relevant literature on the factors of exposure that affect worm infection in humans. Literature search sources include Google Scholar, SpringerLink, PubMed, and ScienceDirect that were published between 2019-2023 and discuss infection exposure agents, organic substances, and the relation between personal hygiene and intestinal worm infection. The research design can be qualitative or quantitative, involving observation, randomized control trials, and case studies. This study involves a population of farmers and uses articles in Indonesian and/or English. The literature review result indicate the importance of personal hygiene, good sanitation, and access to clean water in preventing Soil-Transmitted Helminth (STH) infections among farmers. Awareness of personal hygiene practices and the use of personal protective equipment (PPE) need to be improved to reduce the risk of infection. Furthermore, sanitation and water sources improvement, as well as specific education, are needed to ensure the health of farmers living in rural, urban, and peri-urban areas. The role of nurses in preventing worm infections among farmers in rural areas includes education on sanitation, hygiene practices, and the use of protective equipment. Nurses also need to conduct regular health monitoring, collaborate with other healthcare teams, and improve communication with local health institutions. They should stay updated with research developments and implement the findings in the practice of care and education for farmers and the community.